Performance of La0.6Sr0.4Co1−yFeyO3 (y=0.2, 0.5 and 0.8) nanostructured cathodes for intermediate-temperature solid-oxide fuel cells: Influence of microstructure and composition - Mejía Gómez, Augusto Enrique; Sacanell, Joaquin Gonzalo; Leyva, Ana Gabriela; Lamas, Diego German (Elsevier, 2016)
Fil: Mejía Gómez, Augusto Enrique. Comision Nacional de Energia Atomica. Gerencia del Area Investicaciones y Aplicaciones No Nucleares; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de San Martin. Escuela de Ciencia y Tecnología. Centro Internacional de Estudios Avanzados.; Argentina